SUGGESTOPEDIA: HOW DOES IT ACCELERATE LANGUAGE LEARNING - Katharina Rustipa (Universitas Dian Nuswantoro, 2011)
Suggestopedia is a method of teaching a foreign language in which students learn quickly by being made to feel relaxed, interested and positive. The method is developedÂ  because of the argument that students naturally face psychological barriers to learning. The psychological barriers here refer to a variety of internal distractions (worry, anxiety, fatigue, boredom, fear, etc.). Suggestopedia uses four main stages as follows: presentation, active concert, passive concert, and practice. The design of suggestopedic instruction has positive cognitive, motivational, emotional, and social effects on the learners. Keywords: Suggestopedia, suggestopedic instruction, active concert, passive concert, psychological barriers.